REPRESENTASI RADIKALISME DAN DERADIKALISME AGAMA DALAM SASTRA PESANTREN - Pujiati, Hat (Sunan Kalijaga State Islamic University Yogyakarta, 2018)
Radicalism is not only a challange to a nation-state system but also a threat to the diverse and tolerance of Indonesian. Even literary works are potential to be a site of meanings that fertilizes radicalism through narrations. Therefore, this article scrutinizes the ability of literary texts to support or to counter radicalism in Indonesia. The chosen Sastra Pesantren (Pesantren literature) in this research are Menggapai Kosong by Izzul Muttaqin and Rebbe by Laila Haqy. The focus of this research is ideological position of the author in presenting religious-humanist discourse as a formula of antiradicalism. The analysis is done through a mapping of religious-humanist discourse in the literary texts with considering historical moment and place of the production. Stuart Hall’s representation theory is used in this article. Through constructionist approach this research analyzes the ability of language system in contructing concepts in our minds or to make the material world is meaningfull. The result of this analysis shows that the two pesantren literary works has represented deradicalism as efforts to against religious radicalism. The policies of the government in fighting radicalism have important roles in constructing the divinity and culture of society as recorded by the Pesantren literature.